Emotion, Affect and Personality in Speech : The Bias of Language and Paralanguage - Johar, Swati (United State America Springer, 2016)
This book explores the various categories of speech variation and works to draw a line between linguistic and paralinguistic phenomenon of speech. Paralinguistic contrast is crucial to human speech but has proven to be one of the most difficult tasks in speech systems. In the quest for solutions to speech technology and sciences, this book narrows down the gap between speech technologists and phoneticians and emphasizes the imperative efforts required to accomplish the goal of paralinguistic control in speech technology applications and the acute need for a multidisciplinary categorization system. This interdisciplinary work on paralanguage will not only serve as a source of information but also a theoretical model for linguists, sociologists, psychologists, phoneticians and speech researchers.
Include index
Keywords: Signal processing; Image processing; Speech processing systems; Computational linguistics; User interfaces (Computer systems).; Signal, Image and Speech Processing; Computational Linguistics; User Interfaces and Human Computer Interaction